PROTECTION OF THE RULE OF LAW AS A CONSTITUTIONAL PRINCIPLE AND INDIVIDUAL RIGHT BY THE CONSTITUTIONAL COURT OF KOSOVO - Remzije Istrefi; Bekim Sejdiu (Pravni Vjesnik)
This article examines the case law of the Constitutional Court of Kosovo and explains how this court protects the rule of law, as a fundamental constitutional principle and as a human right. The example of Kosovo is intriguing because of the peculiar historical, political and legal backdrop against which the Constitution was drafted, and the constitutional adjudication that has taken place. Methodologically, this analysis is based on a review of the landmark cases when the Constitutional Court of Kosovo reasoned its decisions with reference to the specific constitutional provisions that enshrine the principle of the rule of law. The paper highlights that the Constitutional Court of Kosovo refers to the rule of law as a general normative framework for adjudicating cases of abstract constitutional review, as well as for deciding cases submitted by individuals – mostly in conjunction with the right to a fair and impartial trial. By scrutinizing the cases of Kosovo, this analysis highlights the role of constitutional courts in ensuring that general constitutional principles, such as the rule of law, are justiciable and have practical effect for human rights of individuals.